Socio-Economic Heterogeneity and Income Distribution: Evidence from Common Property Resource Management (Journal of Forest and Livelihood, 2024)
The author assesses the relationship between socio-economic heterogeneity and equity of resource distribution by reviewing the theoretical literature. He finds mixed results as regards whether resource management and utilization undercommunity based management is equitable and has the potential for positive impact on the livelihood of very poor and marginalized section of the community. He concludes that inequality among resource users has negative impact on thelocal level collective action. Finally, the author relates the theoretical review findings with observations in community forestry in Nepal, and concludes that equity impact is not positive as a result of inequality among resources users.